John Gibson & Antonio Canova. Rezeption, Transfer, Inszenierung - Frasca-Rath, Anna Sophie (Böhlau, 2018)
The book is dedicated to the sculptor John Gibson (1790-1866) and his relationship with Antonio Canova (1757-1822). It analyses Gibson's early years in Rome, his role in anlgo-roman artistic exchange and his self-fashioning strategy as "Britain's Phidias". Through the examination of extensive source material the study gives insights into Gibson's life and work and opens new perspectives on the broader field of 19th century sculpture.